Islam di India: Sejarah, Dinamika, dan Kontribusinya dalam Membangun Peradaban Multikultural: Islam in India: History, Dynamics, and Its Contribution to the Development of a Multicultural Civilization - Azwar, Azwar; Arif Mashuri; Andi Wawan Mulyawan; Adnan Hasan; Abd. Rahim Yunus; Susmihara, Susmihara (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This study aims to comprehensively examine the historical entry and development of Islam in India, as well as its contributions to shaping the multicultural civilization of the subcontinent. Using a descriptive-qualitative method with a historical approach, the research traces the initial paths of Islamic dissemination, the roles of key figures and Muslim dynasties, and the interaction between Islam and local cultures. Islam first arrived in India through trade and peaceful missionary activities by Arab merchants, followed by the military expedition led by Muhammad bin Qasim in the 8th century. The peak of Islamic civilization in India occurred during the Delhi Sultanate and the Mughal Empire, which not only expanded Islamic rule but also laid strong foundations in governance, social structure, education, and culture. Islam became a major force in India's political and social transformation. However, British colonialism significantly impacted the Muslim community, leading to marginalization and identity conflicts that culminated in the partition of India and Pakistan in 1947. This study concludes that the history of Islam in India reflects a complex process of interaction, acculturation, and social dynamics, offering valuable lessons on tolerance, cultural harmony, and civilizational resilience in pluralistic societies.